The Impact Of Oxytocin Massage On Breast Milk Production In Post Partum Mother In The Clinic Hj. Dermawati Medan - Muthia Sari Mardha; Syafitri, Endriyani; Husna, Mutiara (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
As of 2018, just 44% of babies worldwide were breastfed within an hour of their delivery, based on the World Healthcare Organization (WHO). By the time they are six months old, under forty percent of children worldwide are exclusively breastfed. The purpose of this study is to find out how oxytocin massage impacts postpartum moms' ability to produce breast milk at the Hj Clinic. Dermawati Medan. This investigation applies an experimental approach without a control group, using a single group pretest and posttest. All postpartum women who visited the clinic between the third and seventh days were used as the study population. Dermawati. Five people were used in the purposive sampling technique. Data analysis was carried out by a paired t test, namely comparing the data from the pre-test (before therapy) with the post-test (after treatment). It emerged that the routine findings from the test were crucial. The Shapiro-Wilk test results for before and after the oxytocin treatment demonstrated that the distribution of the data was normal (p value = 0.119 > 0.05) and that the allocation was taken out (p value = 0.006 > 0.05). if so, it can be said that the data is distributed normally.At the Hj Dermawati Clinic, a p value (0.00 < 0.05) was achieved for the Paired Sample T Test results using the mother's milk volume variable both prior to and following the oxytocin massage test. The results of this research illustrate how postpartum mothers at the Hj Dermawati Clinic produce greater amounts of breast milk as an effect of oxytocin massage. It is recommended that mothers and families take oxytocin therapy education so they can carry out the therapy themselves at home at least once a week